Multiple Roles of Tissue Plasminogen Activator in Schizophrenia Pathophysiology - Hoirisch-Clapauch, Silvia; Nardi, Antonio E. (Seminars in Thrombosis and Hemostasis, 2013)
Schizophrenia, a disabling mental disorder, is characterized by brain atrophy, especially in the superior temporal gyrus and the medial temporal lobe, which includes the hippocampus and the amygdala. The model that better explains brain atrophy includes a trigger and a predisposing condition. The trigger is exemplified by illicit drugs or environmental stressors that promote release of substances harmful to the neurons, such as glucocorticoids or noradrenalin. Predisposed patients would have one or more conditions that impair neuronal plasticity and neurogenesis. Evidence indicates that abnormal tissue plasminogen activator (tPA) activity is an important predisposing condition. tPA plays an important role in synaptic regulation and plasticity, and in neurogenesis, being crucial to the biology of memory, learning, and emotions. Several biochemical abnormalities seen in schizophrenics are related to decreased levels or impaired activity of tPA, including deficient dopamine transmission at D1 receptors in the prefrontal cortex, impaired cleavage of a precursor of brain-derived neurotrophic factor into its mature form (mature brain-derived neurotrophic factor), abnormal N-methyl-d-aspartate receptor-mediated signaling, reduced Akt phosphorylation, and abnormal activation of reelin. Clinical conditions related to schizophrenia, such as hyperhomocysteinemia, insulin resistance, and type 2 diabetes mellitus are characterized by a loss of tPA function or decreased tPA levels. This article reviews how low levels or abnormal function of tPA are related to the pathogenesis of schizophrenia.
Keywords: tissue plasminogen activator; neurogenesis; schizophrenia; mechanism of action; pathophysiology